Antimicrobial resistance and molecular characterization of Streptococcus agalactiae from pregnant women in southern China - Huiwu Guo; Maozhang Fu; Qing Peng; Zhuoran Chen; Jun Liu; Yingkun Qiu; Yuanchun Huang (Journal of Infection in Developing Countries)
Introduction: This study aimed to characterize antimicrobial resistance (AMR), molecular determinants of AMR and virulence, as well as clonal relationship of Streptococcus agalactiae isolates from women at 35-37 weeks of gestation in the Chaoshan metropolitan area of southern China.